Physical and organoleptic characteristics of beef rendang from the results of coconut milk substitution with FiberCreme - Ramadhani, Amelia Arum; Widati, Aris Sri; Rosyidi, Djalal (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
This research aims to determine the appropriate substitution treatment of coconut milk with FiberCreme for beef rendang based on physical characteristics and organoleptic. The research material used was silverside beef, coconut milk, FiberCreme, and rendang seasoning. This research used a completely randomized design consisting of P0 (100% coconut milk), P1 (75% coconut milk:25% FiberCreme), P2 (50% coconut milk:50% FiberCreme), P3 (25% coconut milk:75% FiberCreme), P4 (100% FiberCreme) with 4 replications. Data analysis used analysis of variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT) if the results showed significantly different or very significant effects. Parameters measured in this research were pH, color La*b*, and organoleptic (color, aroma, texture, taste, and overall acceptance). The ANOVA results showed that the substitution treatment of coconut milk with FiberCreme had no significant effect (P>0.05) on pH, the color of rendang a* (redness), and organoleptic rendang, but had a very significant effect (P<0.01) on the color of rendang L* (lightness) and b* (yellowness). It can be concluded that the substitution of FiberCreme up to 100% did not have a negative effect, so rendang was generally accepted based on physical and organoleptic properties.Keywords: Beef rendang, coconut milk, FiberCreme, physical quality, organoleptic